Complex treatment of generalized catarrhal gingivitis with precursors of early formation of destructive phenomena in the bone structures of periodontium - Gudaryan А.А.; Struk V.I.; Vatamanyuk N.V. (Medičnì Perspektivi)
The article presents the results of comprehensive rehabilitation of 92 patients with generalized catarrhal gingivitis by creating differentiated programs for prevention and treatment of the disease, depending on the absence or presence of laboratory signs that have not been detected by X-ray, early destructive processes in the bone structures of periodontal tissues. It was revealed that appearance in gums tissue of representatives of the major periodontal bacteria is a precursor to the development of initial stage of generalized periodontitis in it. It was established that the earlier objective indicators of bone resorptive process in periodontal tissues in patients with generalized catarrhal gingivitis is an overproduction of proinflammatory cytokines IL-1.beta and TNF-alpha and the lack of anti-inflammatory cytokine IL-4.